Перегрузочные машины канальных ядерных энергетических реакторов - Андреенко С. Н.; Евсеенков Ю. А.; Константинов Б. А.; Кротов Д. А.; Скворцов В. И. (Москва, Энергоатомиздат, 1986)
Авт. указаны на обороте тит. л.